2017
DOI: 10.21608/bjas.2017.164028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Recent Isolates of Bef Virus in Egypt

Abstract: The present work was conducted to identify and characterize recent isolate of bovine ephemeral fever virus (BEFV) in Egypt. 103 serum samples were obtained from 1600 vaccinated animals in El-Salhia dairy farm during the period of July to August 2015. The 103 animals were found to have non-protective low titers of BEF antibodies (≤2-8) as tested by serum neutralization test (SNT), showing BEF signs (fever; harried respiration; lameness and recumbency). Three buffy coat and five blood plasma samples from the 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The BEF virus can often be identified by viral isolation, serological and molecular tools conducted on a blood sample taken from animals in the acute febrile stage of the disease (OIE, 2008). Our obtained results of SNT which was carried out on serum samples collected from clinically infected cattle showed that all of them had very low titers of BEFV serum neutralizing antibody less than 32, which indicated that such were fully susceptible to the infection with BEF virus(Albehwar et al, 2018 ). The protective level of BEFV antibodies should not be less than 32 to achieve full protection of animals as demonstrated by(Daoud et al 2001; Salah, 2006; Aziz-Boaron et al, 2014).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The BEF virus can often be identified by viral isolation, serological and molecular tools conducted on a blood sample taken from animals in the acute febrile stage of the disease (OIE, 2008). Our obtained results of SNT which was carried out on serum samples collected from clinically infected cattle showed that all of them had very low titers of BEFV serum neutralizing antibody less than 32, which indicated that such were fully susceptible to the infection with BEF virus(Albehwar et al, 2018 ). The protective level of BEFV antibodies should not be less than 32 to achieve full protection of animals as demonstrated by(Daoud et al 2001; Salah, 2006; Aziz-Boaron et al, 2014).…”
mentioning
confidence: 76%
“…Serum neutralization test (SNT) was carried out on serum samples collected from diseased cattle showed that all of them had very low titers of BEF serum neutralizing antibody titers as tabulated in Table (1) indicated that such were fully susceptible to BEF virus infection.…”
Section: Immune Status Of Diseased Cattlementioning
confidence: 99%